Analisis Hukum Pidana Terhadap Tindak Pidana Kekerasan dalam Rumah Tangga: Pendekatan Restoratif - Rogie Garcia Junior; Muhamad Marpin Putra; Muhamad Fatih Azzam; Asmak Ul Hosnah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
The crime of domestic violence (DV) is a serious issue that affects the welfare of individuals and society. The results showed that the causes of domestic violence include psychological, economic, and social factors, as well as cultural norms that support violence. In addition, law enforcement often experiences obstacles, such as a lack of understanding of the law, stigma against victims, and limited resources. In the context of criminal law, the restorative approach focuses on victim recovery and offender rehabilitation, which is considered more humane than the retributive approach. The research method used in the preparation of this journal is legal research based on the Library Research method. The search in question is to find good and correct knowledge in the form of secondary, primary and tertiary legal materials that can be used to answer questions from ignorance and solve certain problems and to find systematic and consistent answers. In this research the author takes the formulation of problems such as: 1. How can the restorative approach be applied in handling domestic violence cases? 2. What are the impacts of applying restorative justice on victims and the rehabilitation of offenders, both in terms of positive and negative effects, and an analysis from the perspectives of relative punishment theory and utility theory?